2011
DOI: 10.5423/ppj.2011.27.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Detection of Potato leafroll virus by Reverse Transcription Loop-mediated Isothermal Amplification

Abstract: A new reverse transcription loop-mediated isothermal amplification (RT-LAMP) method for the Potato leafroll virus (PLRV) was developed and compared with conventional reverse transcription polymerase chain reaction (RT-PCR) to address its advantages over RT-PCR. RT-LAMP primers were designed from the open reading frame 3 (ORF3) sequence of PLRV. The RT-LAMP reactions were conducted without or with a set of loop primers. By real-time monitoring using Turbimeter, the RT-LAMP (with loop primers) detects PLRV in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Colorimetric (Goto et al 2009) and fluorescent (Tomita et al 2008) variants of the assay were also developed. RT-LAMP has been used to detect various pathogens, including plant viruses such as Plum pox virus (Varga and James 2006), Potato leafroll virus (Ahmadi et al 2013;Ju 2011), Bean pod mottle virus (Wei et al 2012), Cassava brown streak virus (Tomlinson et al 2013), Pepino mosaic virus (Hasiów-Jaroszewska and Borodynko 2013), Papaya leaf distortion virus (Shen et al 2014) and Cucurbit chlorotic yellows virus (Wang et al 2014). The agarose gel based and turbidimetric variants of the method were also adopted for detection of PVY (Nie 2005;Zhao et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Colorimetric (Goto et al 2009) and fluorescent (Tomita et al 2008) variants of the assay were also developed. RT-LAMP has been used to detect various pathogens, including plant viruses such as Plum pox virus (Varga and James 2006), Potato leafroll virus (Ahmadi et al 2013;Ju 2011), Bean pod mottle virus (Wei et al 2012), Cassava brown streak virus (Tomlinson et al 2013), Pepino mosaic virus (Hasiów-Jaroszewska and Borodynko 2013), Papaya leaf distortion virus (Shen et al 2014) and Cucurbit chlorotic yellows virus (Wang et al 2014). The agarose gel based and turbidimetric variants of the method were also adopted for detection of PVY (Nie 2005;Zhao et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other techniques of PLRV detection, the proposed silver-enhanced LFIA is more sensitive than previously-described LFIAs in conventional format with an LOD of 30 ng/mL (Kondakova, Butenko, Skurat, & Drygin, 2016) and more rapid than tissue print immunoassay with a duration of 4-5 h (Samsatly, Jawhari, Najjar, Sobh, & Abou-Jawdah, 2014). Moreover, due to possibility of on-site application, this LFIA is a good alternative for PLRV assays based on reverse transcription polymerase chain reactions (Cating, Funke, Kaur, Hamm, & Frost, 2015;Ju, 2011;Zhang et al, 2017) or loop-mediated isothermal amplification (Ahmadi, Almasi, Fatehi, Struik, & Moradi, 2013;Almasi, Manesh, Jafary, & Dehabadi, 2013).…”
Section: Comparison Of Lfias Without Enhancement and With Silver Enhamentioning
confidence: 97%
“…The fluorescently labeled amplified product can be quantified using a fluorescence reader, which is light weight, weather-proof, battery operated, GPS enabled, and offers rapid, on-farm end-point detection. Subsequently, RT-LAMP method has been developed for detection of Potato leaf roll virus [9], Pepino mosaic virus [10], Tomato torrado virus [11], and Southern tomato virus [12]. Warghane et al [13] showed the sensitivity of RT-LAMP is 100 times more than RT-PCR using the RNA extracted from the CTV infected leaf samples.…”
Section: Introductionmentioning
confidence: 99%